81.4k views
21 votes
Guys please which one is the right answer

Guys please which one is the right answer-example-1
User Romes
by
4.5k points

2 Answers

10 votes

Answer:

B. Infinitely many solutions.

Explanation:

8(x - 4) = 2(4x - 16)

^--This is the original equation.

If we replace x with 1...

we have the same equation, but we add an extra set of brackets. (You'll see why in a second)

8(1 - 4) = 2{4(1) - 16}

1 - 4 = -3

We start by subtracting 4 from 1. When using positive numbers, we can't do this, however. This gets us to -3. leave it in the parenthesis though!

8(-3) = 2{4(1) - 16}

4(1) = 4

Now, the reason we made an extra set of brackets is because 4x is asking you to multiply 4 by x. but as a number, you have to make an extra set of parenthesis to show that. 4 x 1 = 4 so it stays as a 4.

8(-3) = 2(4 - 16)

^-- Now, we are given this new equation. We'll move away from 8(-3) for just a second, to finish the other parenthesis. But still don't remove the parenthesis for 8(-3)!

4 - 16 = -12

We know that 4-16 would also not be possible with positive numbers, but for this equation, as said before.. you're using negative numbers. so 4 - 16 = 12

8(-3) = 2(-12)

^-- And again, we have a new equation. 8(-3) = 2(-12). Don't remove the parenthesis, as I have said before.

8(-3) = -24

Again, the equation shows with parenthesis, it wants us to multiply. Now we take 8, and multiply it by -3. This is a bit tricky, as it is with negative numbers. But in the end, you should have -24.

-24 = 2(-12)

^--The equation becomes -24 = 2(-12). We'll have to multiply again, so keep the parenthesis.

2(-12) = -24

2(-12) Is also asking you to multiply, so now we do the same as before, which again, is a bit tricky because we are using negative numbers. You should end up with -24 though.

-24 = -24

^--Now, you have -24 = -24. This is true since both are the same number.

8(x - 4) = 2(4x - 16)

^-- Here's our wonderful equation again! Let's replace X with a 2 this time!

If you don't understand, read the tips from above to understand what I'm doing in the following equations!

8(2 - 4) = 2{4(2) - 16}

2 - 4 = -2

8(-2) = 2{4(2)-16}

4(2) = 8

8(-2) = 2(8 - 16)

8 - 16 = -8

8(-2) = 2(-8)

8(-2) = -16

-16 = 2(-8)

2(-8) = -16

-16 = -16

And again, we get the same two numbers!

Hope I helped! <3

User Mr Stinky
by
4.9k points
10 votes

Answer: I think the answer is B

Explanation:

8(x-4) = 8(1-4) = 8-32

2(4x-16) =2(4*1-16) = 8-32

8(x-4) = 8(2-4) = 16-32

2(4x-16) = 2(4*2-16) = 16-32

User Mehraban
by
4.9k points